2014
DOI: 10.3109/07420528.2014.950738
|View full text |Cite
|
Sign up to set email alerts
|

Lunar cycles at mating do not influence sex ratio at birth in horses

Abstract: It is scientifically demonstrated that lunar cycles have important effects on several biological events. Controversy exists about the lunar influence on human and animal parturition. In addition, in the horse industry, especially in Polo Horse breeders of Argentina and around the world there is a higher demand for female offspring than for males. The objective of this study was to determine whether there is a significant association between the lunar phase at the time of mating and the sex ratio at birth in ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…However, the significance of the effects of the moon phase and weather conditions on physiology is a subject that arouses controversy within the scientific community, given the disparity of the results found. Several studies that have been carried out with regard to this applied field have concluded the effects were not statistically significant or the modeled size of the effect was not consistent enough so as for a clinical implication to be determined [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the significance of the effects of the moon phase and weather conditions on physiology is a subject that arouses controversy within the scientific community, given the disparity of the results found. Several studies that have been carried out with regard to this applied field have concluded the effects were not statistically significant or the modeled size of the effect was not consistent enough so as for a clinical implication to be determined [ 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…in the absence of birth limitation methods). 6 One study showed that the sex ratio was not statistically related to different lunar phases or days, 5 although others favor the strong evidence that the offspring sex ratio varies with the time of conception within the cycle. 6 The third question regards whether higher coitus rates inadvertently skew the M/F ratio in favor of an excess of males.…”
mentioning
confidence: 98%
“…5 In fact, there is a large body of research on the variation of human sex ratios based on: (1) the time of insemination within the mother's fertile cycle; (2) the duration of gestation; (3) coital frequency, here called the "coital rate"; and (4) the amount of time taken to achieve conception within a period of risk (viz. in the absence of birth limitation methods).…”
mentioning
confidence: 99%